Partitive Articles and Indefinites, Micro and Macrovariation - Francesco Pinzin; Cecilia Poletto (Studia Linguistica, 2022)
This introductory paper provides an overview of the main phenomena investigated in this Special Issue, such as the relation between the encoding of indefinites and the presence of genitive and definite markers, the relation between partitivity and indefiniteness and the distribution of these phenomena in minority, or “micro”, varieties – such as Italian dialects, Galloromance varieties, North and South Saami – compared to the distribution of the same phenomena in majority, or “macro”, varieties – such as French, Italian, Spanish, Brazilian Portuguese, Estonian, Finnish, Czech and Serbian. The second part of the paper, then, provides an overview of the content of each original paper collected in the special issue.